Optical and Magnetic Studies on Cu2O/PANI Nanocomposite Prepared by Chemical Polymerization Method. (21st January 2014) - Gopalakrishnan, K.; Ramesh, C.; Elango, M.; Thamilselvan, M.
Abstract : Polyaniline embedded green copper oxide (Cu2 O/PANI) nanocomposite has been synthesized through in situ chemical polymerization method in acidic medium at room temperature. The structural, optical, and magnetic properties of Cu2 O/PANI nanocomposite were investigated through Fourier transform infrared spectroscopy (FTIR), UV-Vis absorption spectra (UV-Vis spectra), scanning electron microscopy (SEM), photoluminescence spectra (PL), and vibrating sample magnetometer (VSM). FTIR spectra confirmed the formation of Cu2 O/PANI composite through the shifting of vibrational peaks of PANI and green Cu2 O nanoparticles at 825, 1142, 1299, 1499, 1573 cm −1 and 695 cm −1 respectively. SEM analysis revealed that many aggregations of well-separated irregular shape of Cu2 O nanoparticles with diameter about 15–40 nm exist in the composite matrix. Optical absorbance studies further confirmed the formation of composite through the blue shift of absorption peaks of PANI and diminishing intensity peak of Cu2 O. Cu2 O/PANI nanocomposite demonstrates semiconducting as well as diamagnetic behavior like PANI and Cu2 O nanoparticles. The nanocomposite exhibits high relative photoluminescence intensity in blue as well as green-yellow region of visible spectrum. The optical band gap value from absorption coefficient data is found to be 3.23 eV.